Exploration of Binding Interaction of Steroidal Drugs with HMG-CoA Reductase for the Treatment of Breast Cancer Patients who suffer with Cardiovascular Problems: In-silico Studies - Ahmad, Varish (Asian Pacific Journal of Cancer Biology, 2020)
Introduction: HMG-CoA reductase is widely used as a significant target to screen cardiovascular therapeutics molecules because of its involvement in cholesterol synthesis and cell proliferation. Steroidal drugs like anastrozole, exemestane, letrozole have been tested as potential inhibitors of cancer mediated aromatase enzyme and these could be inhibited to HMG-CoA reductase so that the link with cholesterol synthesis and cell proliferation can be utilized to control cancers in. Objective: To test the binding affinity and binding patterns using computational methods of these drugs and established them as a HMG-CoA reductase inhibitor due to the involvement of this enzyme with cholesterol synthesis and cell proliferation can be utilized to control the cancers. Materials and methods: Freely available docking tools like AutoDock and web resources like DrugBank and PDB were used to extract data and conduct the study. Results: The binding interaction of exemestane has shown significant docking interactions which are followed by anastrozole and letrozole. Exemestane has shown binding energy -8.74 kcal/mol, hydrogen bond length: 1.97513 Å, and interacting amino acid was analyzed as A: ASN658:HD21-: UNK1: O6. The positive control statin was used in this study has shown significant binding interaction but it was less than tested exemestane. Conclusion: Thus, exemestane can potentially inhibit to HMG-CoA reductase enzyme even stronger than the clinically tested drug statin and would be a good choice for cancer patients. Thus, in vitro laboratory experimentation and in vivo research are necessary to put forward therapeutic repositioning of these drugs so they could be established as a broad spectrum potential anticancer drugs including breast cancer especially for the patient with cardiovascular complications.